Photothermal therapy of cancer cells using novel hollow gold nanoflowers - Han J (Dove Medical Press, 2014)
Jing Han,1 Jinru Li,1 Wenfeng Jia,1 Liangming Yao,2 Xiaoqin Li,1 Long Jiang,1 Yong Tian21Beijing National Laboratory for Molecular Sciences, Institute of Chemistry, 2Beijing Key Laboratory of Noncoding RNA, Institute of Biophysics, Chinese Academy of Sciences, Beijing, People's Republic of ChinaAbstract: This article presents a new strategy for fabricating large gold nanoflowers (AuNFs) that exhibit high biological safety under visible light and very strong photothermal cytotoxicity to HeLa cells under irradiation with near-infrared (NIR) light. This particular type of AuNF was constructed using vesicles produced from a multiamine head surfactant as a template followed by depositing gold nanoparticles (AuNPs) and growing their crystallites on the surface of vesicles. The localized surface plasmon-resonance spectrum of this type of AuNF can be easily modulated to the NIR region by controlling the size of the AuNFs. When the size of the AuNFs increased, biosafety under visible light improved and cytotoxicity increased under NIR irradiation. Experiments in vitro with HeLa cells and in vivo with small mice have been carried out, with promising results. The mechanism for this phenomenon is based on the hypothesis that it is difficult for larger AuNFs to enter the cell without NIR irradiation, but they enter the cell easily at the higher temperatures caused by NIR irradiation. We believe that these effects will exist in other types of noble metallic NPs and cancer cells. In addition, the affinity between AuNPs and functional biomolecules, such as aptamers and biomarkers, will make this type of AuNF a good recognition device in cancer diagnosis and therapy.Keywords: HeLa cells, endocytosis, cytotoxicity, AuNFs, NIR, cancer therapy